2023
DOI: 10.3390/vaccines11020242
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Responses against BQ.1.1 Elicited after Breakthrough Infection and SARS-CoV-2 mRNA Vaccination

Abstract: The Omicron BQ.1.1 variant is now the major SARS-CoV-2 circulating strain in many countries. Because of the many mutations present in its Spike glycoprotein, this variant is resistant to humoral responses elicited by monovalent mRNA vaccines. With the goal to improve immune responses against Omicron subvariants, bivalent mRNA vaccines have recently been approved in several countries. In this study, we measure the capacity of plasma from vaccinated individuals, before and after a fourth dose of mono- or bivalen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In the general population, humoral responses are efficiently generated after the SARS-CoV-2 mRNA vaccine and increased after vaccinal boosts [ 16 , 29 , 42 ]. These responses are important since the neutralizing activity of antibodies elicited after vaccination is central to protect and predict the immune response to the SARS-CoV-2 infection [ 33 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, humoral responses are efficiently generated after the SARS-CoV-2 mRNA vaccine and increased after vaccinal boosts [ 16 , 29 , 42 ]. These responses are important since the neutralizing activity of antibodies elicited after vaccination is central to protect and predict the immune response to the SARS-CoV-2 infection [ 33 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increased rate of VOCs, several studies have shown decreased neutralizing capacities of antibodies elicited after mRNA vaccination against the different Spikes [ 15 , 42 , 46 ]. However, antibodies’ Fc-effector functions, such as ADCC, are part of the immune response and help clear the viral infection [ 25 , 40 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies, including this one, showed that the new variants have different degrees of resistance to neutralization induced by vaccination. However, although there is an important circulation of the variants in the population, no increase in the number of severe forms of COVID-19 were observed, indicating that the vaccines remain effective [ 16 , 20 , 29 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids encoding the SARS-CoV-2 D614G, BA.1, BA.4/5, and BQ.1.1 Spike variants were previously described [ 10 , 20 , 33 ]. The pNL4.3 R-E-Luc plasmid was obtained from the NIH AIDS Reagent Program (cat# 3418).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation